2007
DOI: 10.1111/j.1465-7295.2007.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Casino Gaming With Special Reference to a Smoking Ban

Abstract: "This study adds to the limited literature on the demand for casino gaming. The major focus is on the effect of a statewide smoking ban. A system of slot machine demand equations, one each for the three Delaware racinos (racetrack casinos), was developed. The number of slot machines at a racino, at competing in-state racinos, and income were significant demand determinants. Competing out-of-state gaming venues had insignificant effects on gaming demand over the study period. The smoking ban had a significant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
(61 reference statements)
2
19
0
Order By: Relevance
“…However there is growing indirect evidence to suggest that smoking might increase gambling related behaviors. For example, gamblers who smoke have been shown to spend more when gambling than their non-smoking counterparts do (McGrath et al, 2012a) and there is evidence of a marked decrease in gambling revenues from electronic gaming machines in jurisdictions that have implemented smoking bans in gaming venues (Lal and Siahpush, 2008;Pakko, 2004;Thalheimer and Ali, 2008). Such findings are consistent with recent evidence that nicotine administered via tobacco smoke may enhance the incentive value of non-smoking reward related stimuli (e.g., Attwood et al, 2012;Perkins and Karelitz, 2013).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…However there is growing indirect evidence to suggest that smoking might increase gambling related behaviors. For example, gamblers who smoke have been shown to spend more when gambling than their non-smoking counterparts do (McGrath et al, 2012a) and there is evidence of a marked decrease in gambling revenues from electronic gaming machines in jurisdictions that have implemented smoking bans in gaming venues (Lal and Siahpush, 2008;Pakko, 2004;Thalheimer and Ali, 2008). Such findings are consistent with recent evidence that nicotine administered via tobacco smoke may enhance the incentive value of non-smoking reward related stimuli (e.g., Attwood et al, 2012;Perkins and Karelitz, 2013).…”
Section: Introductionsupporting
confidence: 70%
“…The effects of nicotine on wagering behavior are consistent with observations that acute nicotine can increase the reinforcing value of nonpharmacological stimuli in humans (e.g., Barr et al, 2008;Dawkins et al, 2006) as well as evidence that banning tobacco use from gaming venues leads to a marked decrease in electronic gaming machine profits (Lal and Siahpush, 2008;Pakko, 2004;Thalheimer and Ali, 2008). In contrast to the present findings, we recently reported that acute nicotine administered via inhalers (McGrath et al, 2012b) or lozenges (McGrath et al, 2013) did not impact on VLT gambling.…”
Section: Discussionsupporting
confidence: 52%
“…Specifically, if communities successfully enact workplace, then restaurant, and then bar laws, advocates can engage in an incremental policymaking process, extending coverage by venue, beginning with the least controversial (government workplaces) and building toward the most difficult (bars). 2325 However, if communities enact smoking laws only once or rarely, then it is important to create as strong a policy package as possible. In the latter case, advocates might consider opposing a weak proposed law, because the likelihood of strengthening weak laws or passing additional laws would be low.…”
mentioning
confidence: 99%
“…In the US, there was an intense debate about the economic impacts of the smoking ban in New Jersey in November 2002 (Mandel et al, 2005;Pakko, 2008;Pakko, 2006;Thalheimer and Ali, 2008). Studies of the Illinois smoking ban of 2008 found that the revenue decline of Illinois casinos after 2008 was due to a coincidence of economic recession (Harris et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%